A Visible-NIR Responsive Dye-Sensitized Solar Cell Based on Diatom Frustules and Cosensitization of Photopigments from Diatom and Purple Bacteria. (24th April 2020) - Xiao, Xixiang; Zhang, Xiaobo; Su, Haiyang; Chen, Shicheng; He, Zhihui; Zhao, Chungui; Yang, Suping
Abstract : Diatoms exhibit high solar energy harvesting efficiency due to their remarkably organized, hierarchical micro/nanoporous, light-trapping, and scattering frustules. At present, few studies focus on cosensitization of natural near-infrared dye to expand the spectral response of dye-sensitized solar cells. In this study, the diatom frustule-TiO2 (12 : 5) composite film was prepared and assembled it on the TiO2 electrode. Compared to the single TiO2 layer film, diatom frustule-TiO2 (12 : 5) composite film sensitized by diatom's dye showed the conversion efficiency of 0.719%. To expand the light-harvesting response to near-infrared region spectra, the cosensitized dyes were used to fabricate the visible-near-infrared responsive dye-sensitized solar cells. The cosensitization diatom frustule-TiO2 (12 : 5) composite film exhibited two distinct absorption bands in the near-infrared region and reached a higher conversion efficiency of 1.321%, which was approximately 1.4 or 1.7 folds higher than that of cosensitization double-TiO2 film or single TiO2 layer film, respectively, and approximately 3.7 or 1.7 folds higher than that of the single TiO2 layer film sensitized by diatom dye or purple bacterial dye, respectively. The results showed that the combination between diatom frustule-TiO2 with cosensitization natural dyes could significantly improve the photoelectric performance of visible-near-infrared responsive dye-sensitized solar cells.